2011
DOI: 10.1039/c1an15270j
|View full text |Cite
|
Sign up to set email alerts
|

Measuring gas-liquid partition coefficients of aroma compounds by solid phase microextraction, sampling either headspace or liquid

Abstract: Hydrophobic compounds are important odorants and nutrients in foods and beverages, as well as environmental contaminants and pharmaceuticals. Factors influencing their partitioning within multi-component systems and/or from the bulk liquid phase to the air are critical for understanding aroma quality and nutrient bioavailability. The equilibrium partitioning of hydrophobic analytes between air and water was analyzed using solid phase microextraction (SPME) in the headspace (HS-SPME) and via direct immersion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…This minimum alteration should be reconciled, however, with the need for sensitivity. Because of this, a HS-SPME sampling method has been chosen together with conditions in which the displacement of the equilibrium toward free forms should be minimal [28]. Those conditions include incubation of the sample at 45 • C for 10 min and short extraction (10 min) of the headspace over the unstirred sample with a PDMS/DVB fiber.…”
Section: Extraction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This minimum alteration should be reconciled, however, with the need for sensitivity. Because of this, a HS-SPME sampling method has been chosen together with conditions in which the displacement of the equilibrium toward free forms should be minimal [28]. Those conditions include incubation of the sample at 45 • C for 10 min and short extraction (10 min) of the headspace over the unstirred sample with a PDMS/DVB fiber.…”
Section: Extraction Conditionsmentioning
confidence: 99%
“…For instance, several authors have proposed the direct headspace extraction [27] or the SPME extraction of headspaces using short extraction times to assess the degree of interaction of aroma compounds with the matrix [28][29][30]. These approaches, however, require the previous knowledge of the total concentration of the analyte and need to be complemented by a second method and may have sensitivity problems.…”
Section: Introductionmentioning
confidence: 98%
“…× 14 mm I.D. × 0.13 mm, Metro Gasket, Kansas City, MO), aluminum foil (Reynolds, Richmond, VA), and a PTFE septum of 3 mm thickness inserted into a bimetal (Sn/Al) crimp cap (Restek, Bellefonte, PA) (Lloyd, Dungan, & Ebeler, 2011a). Vials were mixed in an agitator (Gerstel, Linthicum, MD) equipped with temperature control at 300 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…From the headspace concentration, vapor/water and water/micelle partition coefficients, as well as dissolved concentrations in water, could then be determined, given known amounts of total solute and surfactant. We have shown in previous work that such methods are well‐suited for quantifying solute distributions between vapor and water in the absence of surfactant (Lloyd, Dungan, & Ebeler, 2011a), and for measuring solute partitioning into micelles over a wide range of compositions (Lloyd, Kardaras, et al, 2011b), without the need to significantly alter the overall system equilibria. In addition, earlier studies have demonstrated that vapor phase measurements of volatile hydrophobic compounds are effective at accurately and non‐invasively assessing their concentration distribution within aqueous micellar solutions (Christian et al, 1981; Vane et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The SPME extraction time chosen will depend on the method objectives. If sampling of only volatiles in the headspace is desired, without influencing the partitioning of the volatiles from the liquid phase into the headspace, then short sampling times are used (~1 to 5 min) (Lloyd et al 2011). Sampling under these conditions is similar to a static HS extraction (Jung and Ebeler 2003).…”
Section: Sample Preservation and Preparationmentioning
confidence: 99%